Lymphoedema. Issue 2 (February 2019) - Lyons, Oliver; Modarai, Bijan
Abstract: Lymphoedema is caused by inadequate lymphatic drainage leading to an accumulation of protein-rich fluid in the interstitium. The most important initial distinction to be made for classification of lymphoedema is between primary lymphoedema (which has a genetic cause) and secondary lymphoedema. Early diagnosis is essential as many conservative therapies are available and can prevent progression. In the Western world lymphoedema is most commonly secondary to cancer and its treatment. In endemic regions filiariasis is an important cause and a global eradication programme is underway. Recently, great progress has been made in understanding the embryology of the lymphatic system and the specific genetic causes of primary lymphoedema, leading to the hope that medical therapies may enable improvement in lymphatic function. Surgery is currently reserved for advanced disease and is performed in specialist centres, primarily to reduce the bulk of swollen tissue.